Notes and News - Tracey, Hugh (International Library of African Music, 1960)
Lords of the Forest - Spirit of Africa - International Folk Music Council - African contemporary art - African music in London - Fiunders Day in Ghana - Celebration dancing in Nigeria
Keywords: African Music